RFID Tracking Evacuation System - Danial, Muhammad Adam; Ismail, Muhammad Nafis (Evolution in Electrical and Electronic Engineering, 2025)
Ensuring the safety of building occupants and keeping track of their presence during emergencies can be a challenging task, especially in office or high-traffic environments. This project presents a practical and cost-effective RFID-based system designed to manage attendance and support evacuation processes. Using the ESP8266 microcontroller and long-range UHF RFID readers, the system records check-in and check-out data in real time, identifying individuals who are still inside during an evacuation. The data is stored locally using SPIFFS, allowing the system to function reliably even without internet access. A simple web-based interface is used to display the status of occupants and access attendance logs. Additionally, the system includes an automatic control logic that focuses on managing energy consumption, particularly for air conditioning units, based on occupancy. The system promotes electricity savings by integrating automatic load switching, particularly for air conditioning units. This ensures that electrical loads are only active when necessary, helping to reduce energy consumption in unoccupied areas.